Method for simply synthesizing ferromanganese phosphate precursor and positive electrode material in liquid phase
Through the simple liquid phase synthesis method, the problems of Fe/Mn ratio inconsistency and low conductivity of the positive electrode material of lithium manganese iron phosphate in large-scale production are solved, and the high-performance preparation of nano-level lithium manganese iron phosphate is achieved, which improves the battery The ratio and cycle life simplify the production process.
Patent Information
- Application Number
- CN202411319224.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2025-01-07
AI Technical Summary
In the mass production of lithium manganese iron phosphate positive electrode materials, there are problems such as inconsistency in the Fe/Mn ratio, low electronic conductivity and uneven particle size distribution, resulting in insufficient rate performance and cycle life of the finished product, and it is difficult to scale with traditional solid-phase synthesis method. Chemical production.
By using the simple liquid phase synthesis method, the manganese source, iron source and phosphorus source are mixed in a specific proportion, and oxidizing agent is added to stabilize the uniform crystallization of the elements, the pH value and temperature are controlled to form a nano-scale sheet-like ferromanganese phosphate precursor, and By adding lithium source and carbon source sintering under an inert atmosphere, lithium manganese iron phosphate positive electrode material with good conductivity and uniform particle size is obtained.
It realizes the uniformity of the material's morphology and concentration of particle size distribution, improves the overall performance of the battery, enhances the material's gram capacity and tap density, solves the ratio performance and cycle life of the finished product, and simplifies large-scale production. process.
Smart Images

Figure CN119263241A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and relates to a method for synthesizing a liquid phase simple lithium iron manganese phosphate precursor, and further preparing a nano-scale high-rate and high-energy-density lithium iron manganese phosphate positive electrode material using the precursor as a raw material. Background Art
[0002] Lithium-ion batteries are composed of many components, among which the positive electrode material determines the battery's charge and discharge performance. The current market requires a positive electrode material with high energy density, long cycle life and good safety. Olivine manganese iron phosphate lithium positive electrode material is a typical representative, with a chemical formula of LiMn x Fe 1-x PO 4 , with a theoretical specific capacity of 170 mAh / g. Due to its wide sources, good stability, and high specific energy, it has become a research hotspot in recent years. Compared with lithium iron phosphate materials, lithium manganese iron phosphate exhibits a voltage platform of 4.1 V due to the presence of Mn atoms, making the energy density of lithium manganese iron phosphate 15% to 20% higher than that of lithium iron phosphate, which is the advantage of lithium manganese iron phosphate. Pure lithium manganese phosphate will have the Jahn-Teller effect due to the presence of Mn, but lithium manganese iron phosphate has iron ions occupying the site, thus making up for the problem of single manganese dissolution. Therefore, lithium manganese iron phosphate will be a very potential lithium-ion positive electrode material in the future new energy market.
[0003] Although lithium iron manganese phosphate has many advantages, it will encounter many difficulties in its production process: First, the Fe / Mn ratio causes the consistency problem of finished products during mass production; second, due to the incorporation of manganese, the electronic conductivity of lithium iron manganese phosphate is low, and the conductivity needs to be improved to improve the rate performance and cycle life of the finished product; third, the particle size and distribution of the material greatly affect the high current and cycle performance of lithium iron manganese phosphate. The traditional solid phase synthesis method has the advantages of simple equipment and simple process, but it has the disadvantages of large particle size and uneven distribution, which causes the performance of lithium iron manganese phosphate to decline. The hydrothermal method can produce lithium iron manganese phosphate with small particle size and uniform morphology, but its preparation process has high requirements, harsh conditions, poor product uniformity, and large-scale production is difficult. This patent adopts the co-precipitation method to effectively avoid such problems. First, manganese and iron are oxidized and then the acidity is controlled to co-precipitate, thereby achieving atomic-level mixing, and the particle size is controllable, which can greatly improve the material's gram capacity and tap density. Summary of the invention
[0004] In order to overcome the problems of difficulty in controlling the Fe / Mn atomic ratio and uneven element distribution in the liquid phase precipitation method, the present invention provides a method for a liquid phase simple synthesis of a ferromanganese phosphate precursor and its further conversion into a lithium ferromanganese phosphate positive electrode material. The method mixes a manganese source, an iron source, and a phosphorus source in a specific ratio to achieve homogeneous mass transfer. By adding an oxidant, the uniform crystallization of iron and manganese elements is stabilized, so that the precipitation reaction proceeds in a steady state, which is conducive to homogenizing the material morphology, and the particle size distribution is also more concentrated and uniform, which helps to reduce the subsequent internal non-uniformity of the battery, thereby improving the overall performance of the battery. The pH value and temperature are adjusted to obtain nano-scale flaky ferromanganese phosphate, and then by adding a lithium source and a carbon source, sintering under an inert atmosphere to obtain a lithium ferromanganese phosphate positive electrode material with good conductivity, uniform particle size and excellent performance. The specific steps are as follows:
[0005] A) weighing a manganese source, an iron source, and a phosphorus source according to a certain molar ratio, dissolving them in pure water and stirring them evenly, then adding an oxidant, adjusting the pH value with an alkaline solution, heating to a certain temperature, and continuing to stir to form a stable slurry, and finally, filtering, washing, and drying to obtain a nano-sheet manganese iron phosphate intermediate.
[0006] B) The ferromanganese phosphate precursor, lithium source and carbon source are mixed in a certain proportion and dissolved in an organic solvent, and then the mixture is ball-milled and dried to obtain a uniform powder. Finally, it is solid-phase sintered at low temperature under an inert gas, naturally cooled to room temperature, and ground to obtain a carbon-coated lithium ferromanganese phosphate positive electrode material product.
[0007] The iron source used in step A) is one or more of ferrous sulfate, ferrous oxalate, ferrous chloride, ferrous carbonate, ferrous nitrate, ferric hydroxide, and ferrocene; the manganese source is one or more of manganese sulfate, manganese chloride, manganese acetate, manganese oxalate, manganese carbonate, and manganese 2-ethylhexanoate; and the phosphorus source is one or more of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, phosphoric acid, sodium dihydrogen phosphate, diammonium hydrogen phosphate, calcium hydrogen phosphate, and calcium phosphate.
[0008] In step A), the molar ratio of the sum of the manganese source and the iron source to the phosphorus source is 0.5 to 1.3.
[0009] The alkaline solution in step A) is one or more of ammonium hydroxide, potassium hydroxide, sodium hydroxide, sodium bicarbonate, sodium carbonate, and calcium hydroxide; and the pH value is 3 to 14.
[0010] The oxidant in step A) is one or more of hydrogen peroxide, ammonium persulfate, potassium permanganate, sodium percarbonate, potassium dichromate, etc.
[0011] The heating temperature in step A) is 20 ~ 100 °C.
[0012] The drying temperature in step A) is 30 to 120°C; and the drying time is 4 to 24 hours.
[0013] The carbon source in step B) is sucrose, xylitol, polyvinyl alcohol, glucose; the lithium source is one or more of lithium carbonate, lithium chloride, lithium hydroxide, and lithium nitrate.
[0014] In step B), the molar ratio of the lithium source to the ferromanganese phosphate is 1 to 1.6, and the molar ratio of the carbon source to the ferromanganese phosphate is 0.1 to 1.1.
[0015] In step B), the organic solvent is one or more of ethanol, oleic acid and acetone.
[0016] The ball milling time in step B) is 1 to 24 h.
[0017] The drying temperature in step B) is 30 to 120°C; the drying time is 4 to 24 hours.
[0018] The inert gas in step B) is one or more of nitrogen and argon.
[0019] The sintering temperature in step B) is 400 to 700°C; the sintering time is 3 to 24 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the XRD diagram of manganese iron phosphate and lithium manganese iron phosphate in Example 1.
[0021] Figure 2 This is the SEM image of the lithium manganese iron phosphate positive electrode material in Example 1.
[0022] Figure 3 This is a diagram of the buckling performance of the lithium iron manganese phosphate positive electrode material in Example 1.
[0023] Figure 4 This is a diagram of the buckling performance of the lithium iron manganese phosphate positive electrode material in Comparative Example 1. DETAILED DESCRIPTION
[0024] The following examples will further illustrate the implementation methods and schemes of the present invention, but the following examples are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0025] Example 1
[0026] This embodiment provides a method for simply synthesizing a manganese iron phosphate precursor and a positive electrode material in a liquid phase, the method comprising the following steps:
[0027] A) Manganese carbonate, ferrous sulfate and potassium dihydrogen phosphate were weighed in a molar ratio of 0.5:0.5:0.8, mixed in pure water and stirred to mix evenly, and then ammonium persulfate was added dropwise, and the pH value was adjusted to 5 with sodium hydroxide, and the mixture was stirred for 1 to 3 hours to form a slurry. The reaction temperature was 30 to 90°C, and the mixture was filtered under reduced pressure and washed with pure water to obtain pure nano-manganese ferrophosphate, which was dried in a drying oven at 60°C for 24 hours and naturally cooled to room temperature to obtain nano-sheet-shaped manganese ferrophosphate.
[0028] B) Manganese iron phosphate: lithium hydroxide: xylitol were mixed in a ratio of 1:1.2:0.4 to form a mixture, dissolved in ethanol, wet-milled in a planetary ball mill for 1 to 10 h, taken out, dried at 60 °C for 10 h, and heated under N 2 The carbon-coated lithium manganese iron phosphate cathode material was obtained by sintering at 800 °C for 6 h, cooling to room temperature naturally, and grinding.
[0029] Example 2
[0030] A) Manganese chloride, ferrous oxalate and phosphoric acid are weighed according to the iron molar ratio of 0.5:0.5:1, the three are mixed and added into pure water and stirred to mix evenly, potassium permanganate is added dropwise, the pH value is adjusted to 8 with ammonia water, stirring is continued for 1 to 3 hours to form a slurry, the reaction temperature is 30 to 90 ° C, and after reduced pressure filtration, the slurry is washed with pure water to obtain pure nano-manganese ferrophosphate, which is dried in a drying oven at 80 ° C for 24 hours and naturally cooled to room temperature to obtain nano-sheet-shaped manganese ferrophosphate.
[0031] B) Manganese iron phosphate: lithium carbonate: glucose in a ratio of 1:1.4:0.6 were added and mixed to form a mixture, dissolved in oleic acid, wet-milled in a planetary ball mill for 1 to 10 h, taken out, dried at 80 °C for 6 h, sintered at 700 °C for 10 h under argon, cooled naturally to room temperature, and ground to obtain a carbon-coated manganese iron lithium phosphate positive electrode material product.
[0032] Example 3
[0033] A) Manganese sulfate, ferrous chloride and phosphoric acid are weighed in a molar ratio of 0.5:0.5:1.2, mixed and added into pure water and stirred to mix evenly, hydrogen peroxide is added dropwise, and the pH value is adjusted to 12 by potassium hydroxide, and stirring is continued for 1 to 3 hours to form a slurry, the reaction temperature is 30 to 90 ° C, and after reduced pressure filtration, the mixture is washed with pure water to obtain pure nano-manganese ferrophosphate, which is dried in a drying oven at 40 ° C for 24 hours and naturally cooled to room temperature to obtain nano-sheet-shaped manganese ferrophosphate.
[0034] B) Manganese iron phosphate: lithium chloride: sucrose were mixed in a ratio of 1:1.6:0.8 to form a mixture, dissolved in ethanol, wet-milled in a planetary ball mill for 1 to 10 h, taken out, dried at 100 °C for 4 h, and heated under N 2 The product was sintered at 600 °C for 16 h, cooled to room temperature naturally, and ground to obtain the finished carbon-coated lithium manganese iron phosphate cathode material.
[0035] Comparative Example 1
[0036] A) Manganese carbonate, ferrous sulfate and potassium dihydrogen phosphate were weighed in a molar ratio of 0.5:0.5:0.8, mixed into pure water and stirred to mix evenly, and then ammonium persulfate was added dropwise, and the pH value was adjusted to 5 with sodium hydroxide, and the mixture was stirred for 1-3 h to form a slurry. The reaction temperature was 30-90 °C, and the mixture was filtered under reduced pressure and washed with pure water to obtain pure nano-manganese ferrophosphate, which was dried in a drying oven at 60 °C for 24 h and naturally cooled to room temperature to obtain nano-sheet-shaped manganese ferrophosphate.
[0037] B) Manganese iron phosphate: lithium hydroxide: xylitol are mixed in a ratio of 1:1.2:0.4 to form a mixture, dissolved in ethanol, wet-milled in a planetary ball mill for 1 to 10 h, taken out, dried at 60 °C for 10 h, sintered at 800 °C for 6 h under argon, naturally cooled to room temperature, and ground to obtain a carbon-coated manganese iron lithium phosphate positive electrode material product.
[0038] Comparative Example 2
[0039] A) Manganese carbonate, ferrous sulfate and potassium dihydrogen phosphate were weighed in a molar ratio of 0.5:0.5:1, mixed in pure water and stirred to mix evenly, and then ammonium persulfate was added dropwise, and the pH value was adjusted to 8 with sodium hydroxide, and the mixture was stirred for 1 to 3 hours to form a slurry. The reaction temperature was 30 to 90°C, and the mixture was filtered under reduced pressure and washed with pure water to obtain pure nano-manganese ferrophosphate, which was dried in a drying oven at 60°C for 24 hours and naturally cooled to room temperature to obtain nano-sheet-shaped manganese ferrophosphate.
[0040] B) Manganese iron phosphate: lithium carbonate: glucose are mixed in a ratio of 1:1.4:0.6 to form a mixture, dissolved in ethanol, wet-milled in a planetary ball mill for 1 to 10 hours, taken out, dried at 60°C for 10 hours, sintered at 800°C for 6 hours under argon, naturally cooled to room temperature, and ground to obtain a carbon-coated manganese iron phosphate lithium positive electrode material product.
Claims
1. A method for simply synthesizing a manganese iron phosphate precursor and a positive electrode material in a liquid phase, comprising the following steps: A) weighing a manganese source, an iron source, and a phosphorus source according to a certain molar ratio, dissolving them in pure water and stirring them evenly, then adding an oxidant, adjusting the pH value with an alkaline solution, heating to a certain temperature, and continuing to stir to form a stable slurry, and finally, filtering, washing, and drying to obtain a nano-sheet-shaped manganese iron phosphate intermediate; B) The ferromanganese phosphate precursor, lithium source and carbon source are mixed in a certain proportion and dissolved in an organic solvent, and then the mixture is ball-milled and dried to obtain a uniform powder. Finally, it is solid-phase sintered at low temperature under an inert gas, naturally cooled to room temperature, and ground to obtain a carbon-coated lithium ferromanganese phosphate positive electrode material product.
2. According to claim 1), a method for simply synthesizing a ferromanganese phosphate precursor and a positive electrode material in a liquid phase, wherein: The iron source used in step A) is one or more of ferrous sulfate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferric hydroxide, and ferrocene; the manganese source is one or more of manganese sulfate, manganese chloride, manganese acetate, manganese oxalate, and manganese 2-ethylhexanoate; the phosphorus source is one or more of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, phosphoric acid, sodium dihydrogen phosphate, and diammonium hydrogen phosphate; and the oxidant is one or more of hydrogen peroxide, ammonium persulfate, potassium permanganate, sodium percarbonate, and potassium dichromate.
3. The method for liquid phase simple synthesis of ferromanganese phosphate precursor and positive electrode material according to claim 1, wherein: In step A), the molar ratio of the sum of the manganese source and the iron source to the phosphorus source is 0.5 to 1.3; the alkaline solution is one or more of ammonium hydroxide, potassium hydroxide, sodium hydroxide, sodium bicarbonate, sodium carbonate, and calcium hydroxide; and the pH value is 3 to 14.
4. The method for liquid phase simple synthesis of manganese iron phosphate precursor and positive electrode material according to claim 1, wherein: The heating temperature in step A) is 20 to 100°C; the drying temperature is 30 to 120°C; and the drying time is 4 to 24 hours.
5. The method for liquid phase simple synthesis of ferromanganese phosphate precursor and positive electrode material according to claim 1, wherein: The carbon source in step B) is sucrose, xylitol, polyvinyl alcohol, glucose; the lithium source is one or more of lithium carbonate, lithium chloride, lithium hydroxide, lithium nitrate; the organic solvent is one or more of ethanol, oleic acid, acetone; the inert gas is one or more of nitrogen and argon.
6. The method for liquid phase simple synthesis of ferromanganese phosphate precursor and positive electrode material according to claim 1, wherein: In the step B), the molar ratio of the lithium source to the ferromanganese phosphate is 1 to 1.6; the molar ratio of the carbon source to the ferromanganese phosphate is 0.1 to 1.
1.
7. The method for liquid phase simple synthesis of ferromanganese phosphate precursor and positive electrode material according to claim 1, wherein: The ball milling time in step B) is 1 to 24 hours; the drying temperature is 30 to 120°C; the drying time is 4 to 24 hours; the sintering temperature is 400 to 700°C; and the sintering time is 3 to 24 hours.
Citation Information
Patent Citations
Battery grade iron and manganese phosphate and preparation method thereof
CN104518217A
Preparation method of battery-grade iron manganese phosphate, lithium ferric manganese phosphate, battery positive electrode material and secondary battery
CN107697899A
Method for preparing nanoscale lithium ferric manganese phosphate material by using co-crystallization method
CN113659134A
Preparation method of lithium manganese iron phosphate positive electrode material
CN117383533A
Method for preparing battery grade ferromanganese phosphate based on coprecipitation method
CN118026129A
Cited By
Ferromanganese phosphate material and preparation method thereof, positive electrode material and secondary battery
CN120518049A
Manganese-doped flaky iron phosphate as well as preparation method and application thereof
CN121020529A
Surface-functionalized lithium manganese iron phosphate, positive pole piece containing surface-functionalized lithium manganese iron phosphate and battery containing surface-functionalized lithium manganese iron phosphate
CN121506910A